(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1991)
In the present paper, the conodont fauna from three detailed sections surveyed in the Lower Triassic sequence of Central Dolpo, Nepal (Tarap-Atali area) is illustrated. Combining faunas from the three sections, it was possible to recognize a succession of faunal events that covers most of the Scythian and the Lower Anisian. In the whole, 11 faunas have been recognized and discussed.